IMMU-39. TIM-3 APTAMER IN COMBINATION WITH RADIOTHERAPY RESULTS IN ENHANCED SURVIVAL IN DIPG MODELS. (9th November 2020) - Martinez-Velez, Naiara; Garcia-Moure, Marc; Puigdelloses, Montserrat; Laspidea, Virginia; Ausejo, Iker; Ramos, Luis Isaac; Becher, Oren J; Pastor, Fernando; M Alonso, Marta
Abstract: Pediatric diffuse midline gliomas-H3-K27M-mutant are aggressive brain tumours that arise during childhood. Despite new advances in genomic knowledge and the significant number of clinical trial testing new targeted therapies, patient outcome is still insufficient. Cancer immunotherapy is opening new therapeutic options representing a hope for this orphan disease. Aptamers are single-stranded nucleic acid ligands design to achieve a remarkable affinity and specificity to their targets, comparable to antibodies. TIM-3, is a potential immune checkpoint target, typically involved in T-cell exhaustion. Recent studies showed that TIM-3 is also expressed in tumour and glial cells and it plays an important role in brain tumour responses mediated by myeloid cells. In this work, we examined the anti-tumour effect of an aptamer against TIM-3 alone or in combination with radiotherapy. Of importance, we tested TIM-3 aptamer in a murine glioma and DIPG model, where we not observed any toxicity. TIM-3 administration increased overall survival but was unable to control the disease. Of importance, TIM-3 combination with radiotherapy improved the overall survival of treated mice when compared with single treatments leading to 50% of long-term survivors. TIM-3 aptamer administration increase T-infiltration in the tumour site compared to non-treated or library control. Mechanistic studies performed on day 16 showed an increase in CD8 effector cells, a decrease in T-regulators Foxp3+ cells and an increase in IFN-gamma expression suggesting the triggering of an antitumor-immune response. Rechallenge experiments demonstrated immune memory in the long-term responders that led to reject tumour re-implantation, confirming that TIM-3 aptamer treatment in combination with RT elicits specific antitumor immunity in mouse glioma models. These results suggest that immuno-therapies approaches in combination with radiotherapy would be worth exploring in the treatment of deadly DMG-H3K27-Mutant tumours.